Thoracic imaging - Hansell, David; Boiselle, Phillip M.; Goldin, Jonathan; Kauczor, Hans-Ulrich; Lynch, David A.; Mayo, John R.; Patz, Edward F. (Respirology, 2010)
The various techniques encompassed in the term ‘Thoracic Imaging’ have had a dramatic effect on the practice of respiratory medicine over the last 25 years. One of many examples is the increased precision with which lung cancer can be preoperatively staged using CT and PET imaging. The increasing sophistication of thoracic imaging tests brings many benefits, but there are caveats. This review considers a selection of techniques and contains state-of-the-art commentaries by distinguished experts on current challenges and likely future developments.